The Effect Of Service Quality To The Costumer Satisfaction On Domino’s Pizza Branch Grand Centro Bintaro, South Jakarta - Rissa Hanny; Tunggul Jayadih (Universitas Indraprasta PGRI, 2020)
This study aims to determine the effect of service quality on customer satisfaction in Domino’s Pizza Branch Grand Centro Bintaro, South Jakarta. Type of research using survey research. The subject of this study as many as 100 consumer people's Domino's Pizza. Methods of data collection using observation and questionnaire techniques with a Linkert scale. Legitimate of the data obtained by the validity and reliability test, The research findings confirm that there is a positive and significant impact between the service quality to the customer satisfaction in Domino’s Pizza Branch Grand Centro Bintaro, South Jakarta. The coefficient of determination (R)2 is service quality has a strong enough influence on customer satisfaction.